Examination of References in Rosen’s Emergency Medicine Text Book, 8th Edition; an Observational Study - Güven, Ramazan (Archives of Academic Emergency Medicine, 2018)
Introduction: This study aims to analyze the references that the authors and editors used during the writing of Rosen’s Emergency Medicine, 8th edition. Methods: 15,209 references, which were used in 197 chapters of Rosen’s EmergencyMedicine, 8th edition, were examined regarding the distribution of countries, journals, publication year, and the department of the affiliation of the first author. Results: A total of 63.1% (n = 9591) of the references were led by authors from the United States (US). US-based journals were mostly used, and Annals of Emergency Medicine was the journal from which the references were most frequently extracted, with a percentage of 5.2% (n = 756). The studies conducted by emergency physicians have increased in recent years, and emergency physicians, with a percentage of 17.8% (n = 351), were the leading authors of studies conducted between 2010 and 2013, which were cited in the references of Rosen’s Emergency Medicine, 8th edition. Conclusion: US-based studies make up a significantly bigger portion of the references used in Rosen’s Emergency Medicine, 8th edition. If Europe and other countries give due importance to emergency medicine, they will have the capability to produce studies that can be used as references in textbooks asmuch as the US.